Comparison of storage density and efficiency for cascading adsorption heat storage and sorption assisted water storage. (1st March 2020) - Treier, Matthias S.; Desai, Aditya; Schmidt, Ferdinand P.
Abstract: Storage of thermal energy can be important for compensating the mismatch between demand and supply of energy, especially due to fluctuating renewable energy sources. Within this study, two different system concepts of thermal energy storage involving sorption effects are analysed in a simulation study with the aim of increasing storage efficiency and storage density compared to known systems. Both systems indicate a possible benefit in energy density and storage efficiency but it is also analysed how the choice of system boundary and temperature requirements of the use case influence these two figures of merit. Highlights: Efficiency can be increased through cascading adsorption storage. Moderate increase in storage density for cascading adsorption storage. No significant advantage in storage density compared to water storage.